PENGARUH TINGKAT PROFITABILITAS DAN LIKUIDITAS TERHADAP KECUKUPAN MODAL PADA BANK TABUNGAN NEGARA SYARIAH CABANG DIPONEGORO SURABAYA - Nurlailah, Nurlailah (El-Qist: Journal of Islamic Economics and Business (JIEB), 2014)
This study uses secondary data from the financial statements of Islamic State Savings Bank (BTN Syariah) Branch Diponegoro Surabaya per quarter over the period 2010 – 2012. Analytical technique used is multiple linear regressions with a coefficient of multiple determination tests fitted the classic assumptions including relevant test, autocorrelation, normality tests, and heteroskedasticity to make sure that those assumptions are met by the model used in this study. Hypothesis testing uses a t-test for testing the partial regression coefficients and F-test statistics for the simultaneous regression coefficients testing on a significant level of 5%. During the period of observation on the basis of relevant test, autocorrelation, and heteroskedasticity not found variables that deviate from the classical assumptions. In addition, this research indicates the Gaussian normal; this shows that the available data are qualified to use multiple linear regression equations of the model. The results showed that ROA partially influence significantly to CAR because it has a value smaller than 5% (0.05) significance. While ROE and FDR partially do not affect significantly to CAR on Sharia State Savings Bank Branch Diponegoro Surabaya because t-count is smaller than t-tabel. However, simultaneously, ROA, ROE, and FDR proved influential significantly to CAR because it has a value smaller than 0.05 and F-count greater than F-table. The role of the management of assets and liabilities is quite important in generating the level of profitability. Similarly, the performance of the management of liquidity contributes to the achievement of efficiency means that bank. It was followed by pretty invlovement of liability and capital management in boosting the level of efficiency of the bank. Such a condition should be noted by the management of Islamic banks that managerial policies in the above three areas need to be constantly improved because it has been proven to contribute to the efficiency of the Islamic banking business.